Preterm heart in adult life: cardiovascular magnetic resonance reveals distinct differences in left ventricular mass, geometry, and function. - Lewandowski, A; Augustine, D; Lamata, P; Davis, E; Lazdam, M; Francis, J; McCormick, K; Wilkinson, A; Singhal, A; Lucas, A; Smith, N; Neubauer, S; et al. (2013)
BACKGROUND: Preterm birth leads to an early switch from fetal to postnatal circulation before completion of left ventricular in utero development. In animal studies, this results in an adversely remodeled left ventricle. We determined whether preterm birth is associated with a distinct left ventricular structure and function in humans. METHODS AND RESULTS: A total of 234 individuals 20 to 39 years of age underwent cardiovascular magnetic resonance. One hundred two had been followed prospectively since preterm birth (gestational age=30.3±2.5 week; birth weight=1.3±0.3 kg), and 132 were born at term to uncomplicated pregnancies. Longitudinal and short-axis cine images were used to quantify left ventricular mass, 3-dimensional geometric variation by creation of a unique computational cardiac atlas, and myocardial function. We then determined whether perinatal factors modify these left ventricular parameters. Individuals born preterm had increased left ventricular mass (66.5±10.9 versus 55.4±11.4 g/m(2); P<0.001) with greater prematurity associated with greater mass (r = -0.22, P=0.03). Preterm-born individuals had short left ventricles with small internal diameters and a displaced apex. Ejection fraction was preserved (P>0.99), but both longitudinal systolic (peak strain, strain rate, and velocity, P<0.001) and diastolic (peak strain rate and velocity, P<0.001) function and rotational (apical and basal peak systolic rotation rate, P =0.05 and P =0.006; net twist angle, P=0.02) movement were significantly reduced. A diagnosis of preeclampsia during the pregnancy was associated with further reductions in longitudinal peak systolic strain in the offspring (P=0.02, n=29). CONCLUSIONS: Individuals born preterm have increased left ventricular mass in adult life. Furthermore, they exhibit a unique 3-dimensional left ventricular geometry and significant reductions in systolic and diastolic functional parameters. CLINICAL TRIAL REGISTRATION: URL: http://www.clinicaltrials.gov. Unique identifier: NCT01487824.